Internet transparency in developing African regions: case of the DR Congo - Munganga, Dieudonne (Department of Computer Science, 2024)
This thesis investigates internet transparency and connectivity in the Democratic Republic of Congo (DRC) using a combination of secondary data analysis, online surveys, and primary data collected through Internet measurement on personal devices. The research aims to understand the perception of internet performance by the users, the level of interconnection among Autonomous systems and the Quality of Service (QoS) and Quality of Experience (QoE) provided by broadband networks in the DRC, and how it compares to other Central African countries. The research found that users in the DRC have a low level of satisfaction with internet performance and that the country's internet infrastructure and Autonomous systems are not well interconnected, leading to poor network performance. Additionally, the research found that the QoS and QoE provided by broadband networks in the DRC are far from optimal and lower than other Central African countries. Furthermore, the research revealed that there is a lack of transparency in the DRC's internet structure, with certain networks exerting a significant level of influence on users' internet connectivity. These findings indicate a need for increased transparency and improved internet infrastructure in the DRC to better serve the needs of its citizens and support economic and social development. The thesis concludes with a section on future work, highlighting potential avenues for further research such as enhancing the Internet measurement aspect of the study, using machine learning techniques to analyze the data, conducting a study on the impact of internet access and quality on social development, and developing a real-time monitoring system for internet connectivity in the DRC.